The Intercorrelation among EFL Learners' Metacognitive Reading Strategies, Motivation, and Reading Comprehension ability - Moh Sirril Athar; Junaidi Mistar; Imam Wahyudi Karimullah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study aims to predict the relationship among the use of metacognitive reading strategies, motivation, and reading comprehension ability. Thirty-five university students of second semester especially from English Language Department at University of Islam Malang were shared the questionnaires of Reading strategies and motivation followed by answering a reading test. A quantitative method was used with correlational design. The findings implied the students use different strategies when reading text. PROB (Problem-Solving Strategies) was most frequently used in students’ reading activity. They also had high motivation when reading academic text since they are curious about the contents. In reading comprehension aspect, most of students got low predicate or perform below the average. Pearson product moment and spearman rank correlation in SPSS 25 were used to predict the relationship among the variables. The result showed that metacognitive reading strategies cannot be made to predict the increase of reading comprehension ability. Nevertheless, there is a significant correlation between metacognitive reading strategies and motivation. The findings contradict with the findings of most previous studies. Therefore, more investigations need conducting since there are other factors affecting reading comprehension performance such as students’ linguistic knowledge, and also the appropriateness of strategy used. Keywords: reading, metacognitive reading strategies, reading motivation, reading comprehension